Replantation as an Alternative for Multiple Impacted Anterior Teeth After Failed Exposure Surgery - Prasetya, Denta Aditya; Arum, Dena Kusuma (Odonto : Dental Journal, 2025)
Impacted of anterior teeth are generally treated with orthodontic treatment and exposure surgery. This treatment can be performed on anterior teeth with certain inclinations and requires a certain period of time. This case report presents an alternative treatment for impacted of lateral incisive and canine maxillary by dental replantation procedure. Dental replantation is a method of dental treatment that is often performed in dental trauma cases, especially avulsion teeth. This treatment aims to maintain natural teeth that have been lost so that they can be used according to their function. In this case report, anterior teeth of central incisive and canine maxillary had undergone previous orthodontic treatment and exposure surgery, but did not provide significant results. Dental replantation was then chosen as an alternative treatment. The odontectomy procedure was carried out previously by extracted incisive and canine maxillary completely. Treatment continued with interdental fixation using an arch bar and administration of synthetic bone grafts around the roots of lateral incisive and canine maxillary. Replantation is carried out by placing lateral incisive and canine maxillary in the space between the central incisive and premolar maxillary in an underocclusion position. Observation was carried out for 60 days and the one-year evaluation showed satisfactory results. Dental replantation can be used as an alternative treatment for impacted teeth with several requirements in order to get a good final result.